EXPLORING THE SEMANTIC SHIFTS IN TRANSPOSED EPITHETS: A STUDY OF ENGLISH TEXTUAL DEVICES (Neo Scientific Peer Reviewed Journal, 2024)
The study aims to shed light on the motivational factors behind the usage of transposed epithets in English literature. The study intends to delve into the semantic shifts that occur when an adjective is transferred from its conventional noun and analyze the resulting mental spaces and conceptual integration effects. This paper fills a gap in the existing literature by providing insights into the processing and interpretation of transposed epithets, which have been relatively understudied in cognitive linguistics.